Perceptions of the care and support services available for nurses caring for patients with HIV/AIDS in the Intermediate Hospital Oshakati - Shipanga, Vistorine; Augustyn, Johan; Ashipala, Daniel (International Journal of Advanced Nursing Studies, 2017)
Purpose: The rationale of thisresearch was to describe the care and support services given to nurses who are responsible for providing care for patients with both the human immunedeficiency virus. Accordingly, the study investigated HIV/AIDS care support preferences for nurses.Method: The study used a descriptive research design. The respondents comprise twenty-four (24) nurses who were conveniently selected from Intermediate Hospital of Oshakati (IHO).The The requisite data was collected via questionnaires, which were distributed to the respondents. The respondents were required to fill in the questionnaires and furnish their views on their perceptions regarding the care and support services available for nurses caring for patients with HIV/AIDS in the Intermediate Hospital Oshakati.Findings: The study revealed a lack of guidance for nurses who provide care for immunocompromised patients. The study also found that the majority of challenge's nurses face in providing care, and support involved emotional pain and under staff.Conclusions: The study concluded that the nurses themselves were both affected and infected by HIV/AIDSbut that these same nurses are expected to provide treatment to patients with HIV/AIDS. Support systems for nurses constitute an extremely important workplace issue, although the nurses conceded that the hospital in question did not have sufficient capacity to provide such support systems.Recommendations: This study suggested that the hospital leadership could function as a team in developing supportive interventions that match the problems/needs identified. Nurses should also takes to take an active role in caring for themselves.
Keywords: Availability; Care; Patients; Support; Perceptions